Integration of mobile learning in English vocabulary learning in an iranian school in Kuala Lumpur / Ali Jahani - Jahani, Ali (2015)

(untitled)
The purpose of this quasi experimental study was to examine the effectiveness of mobile (SMS) learning on Iranian EFL learners‟ English vocabulary learning. In addition, this study compared two approaches of vocabulary learning, namely, SMS learning and paper text learning in an Iranian school in Kuala Lumpur. The media richness theory (Daft & Lengel, 1986), Bloom‟s Taxonomy theory (Anderson, 2001) and Motivation theory (Keller,1987) were chosen as the theoretical foundation for this study. Furthermore, this study investigated whether there was any significant difference between the control and experimental groups of participants regarding their learning and satisfaction scores. Finally, the study also tried to investigate the relationship between the participants‟ vocabulary learning and satisfaction scores. The present study was conducted in an Iranian school in Kuala Lumpur, Malaysia. Indeed,41 students from two third grade classes, with the same teacher, were selected based on convenience sample procedure to establish the samples for collecting the quantitative data. In order to provide interview data, six learners who had participated in the experimental group were purposefully selected as the interviewees of the study. They were interviewed to identify why SMS learning can affect their vocabulary and satisfaction with learning. The age of students ranged from 16 to 17 years. This study adopted t-test, ANCOVA, and correlation coefficient to analyze the data obtained from the standard tests and questionnaires. For interview analyzing, inductive thematic analysis was used. In addition, the findings revealed that learning of vocabulary by SMS resulted in significant differences in the learning and satisfaction scores between the control and experimental groups. Furthermore, the results indicated a positive medium correlation between learning and satisfaction scores of the learners in the experimental and control iv group. In conclusion, findings based of data showed that learning by SMS could be used as a complementary strategy in the learning of English vocabulary among EFL learners due to some of its capabilities such as its availability anywhere and anytime besides being an attractive method for learners.